Board Independent, Firm Size, CEO Ownership and Accounting Conservatism: Evidence Banking Company in Indonesia - Ardiany, Yuli; Lukviarman, Niki; Hamidi, Masyuri; Luthan, Elvira (AIBPM Publisher, 2023)
The aim of this study is to provide empirical findings regarding a range of determinants that may impact accounting conservatism. Specifically, the research will examine the effects of company size, CEO ownership, and independent boards. Secondary data, specifically information derived from annual financial reports, is utilised in this study. Information for financial reports is acquired from the IDX data stream and website. From 2013 to 2022, the population of this study comprises all banking institutions listed on the Indonesia Stock Exchange. Significantly positive effects of board independence and company size on accounting conservatism are demonstrated by the findings of this study. Furthermore, CEO ownership has a significant negative impact on accounting conservatism, according to the findings of this study. The findings of this study present a practical illustration for stakeholders regarding the responsibilities of shareholders, which may prove beneficial in overseeing the organization's operations. This research demonstrates that when a company is owned by its CEO, its conservatism decreases. The findings of this research have implications for decision-makers who rely on financial reports. Stakeholders can place trust in managers who provide information about the company through financial reports that reflect its condition. This is supported by the research results, which indicate that conservatism in practice corresponds to the political cost hypothesis, which states that as the size of a company increases, so does conservatism.